Public Policy Communication in The Process of Implementing The Independent Learning Program for Remote Indigenous Peoples of Parigi Moutong Regency - Nurlina, Nurlina; Khairil, Muhammad; Liwesigi, Fadhliah; Lampe, Ilyas; Hatta, Ikhtiar (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to determine public policy communication in implementing the Freedom of Learning policy in Remote Indigenous Peoples of Parigi Moutong Regency. This study uses a qualitative and case study approach conducted in West Lombok Village, Tinombo District, Parigi Moutong Regency. The research involved seven educational units, namely: 1) Ogopuyo Hamlet Independent Play Group, 2) Gianang Hamlet Remote Play Group, 3) Bolo Hamlet Bright Kindergarten, 4) Alkhairat Refugee Elementary School Gianang Hamang, 5) Babong Hamlet Remote Elementary School, 6) Yapintar Nature School, and 7) PKBM Mahakarya. The study results show that public policy communication in implementing the Freedom to Learn policy in the Remote Indigenous Peoples of Parigi Moutong Regency has not gone well. Socialization and assistance related to the Independent Learning Policy by regional policyholders are rarely carried out, hindering the development of an independent education system. Difficult communication access and remote geographical location are some of the factors hindering bureaucratic communication. In addition, implementing the Freedom to Learn policy at the PAUD, SD, and PKBM levels in West Lombok villages is not running to launch the policy. Communication in remote Indigenous communities faces unique barriers due to geographical, cultural, and technological limitations. Common obstacles faced include geographical distance, language and culture, limited access to technology, low levels of education, lack of awareness about the importance of communication, and mistrust or social problems.